Efficacy and safety of levodopa–carbidopa intestinal gel from a study in Japanese, Taiwanese, and Korean advanced Parkinson’s disease patients - Murata, Miho (NPJ Parkinsons Dis, 2016)
In a previous multinational, randomized, double-blind, double-dummy study, levodopa–carbidopa intestinal gel (LCIG) was tolerable and significantly improved ‘off’ time in advanced Parkinson’s disease (PD) patients. However, efficacy and safety in the Asian population has not yet been demonstrated. In this open-label study, efficacy and safety of LCIG were assessed in Japanese, Korean, and Taiwanese advanced PD patients with motor complications not adequately controlled by available PD medication. The patients were treated with LCIG monotherapy for 12 weeks. The primary end point was the mean change from baseline to week 12 in ‘off’ time, as reported in the PD Symptom Diary, normalized to a 16 h waking day and analyzed by a mixed-model repeated-measures analysis. Adverse events (AEs) were recorded. Thirty-one patients were enrolled (23 Japanese, 4 Taiwanese, 4 Korean) and 28 (90%) completed the study. For those who completed the study, the mean (s.d.) total daily levodopa dose from LCIG was 1,206.3 (493.6) mg/day at final visit (n=28); last observation carried forward (n=30) was 1,227.6 (482.8) mg/day. There was a significant mean change (s.d.) of −4.6 (3.0) hours of ‘off’ time from baseline (mean (s.d.)=7.4 (2.3)) to week 12 (n=29), P<0.001. All the patients had an AE, with the most frequently reported being incision site pain (42%); 1 (3.2%) discontinued treatment because of an AE and later died because of sepsis, which the investigator considered unrelated to LCIG treatment. These results suggest that LCIG is efficacious and tolerable in Japanese, Taiwanese, and Korean advanced PD patients.